Spiritual care as a secular profession: politics, theory, and practice - Lasair, Simon (Journal for the Study of Spirituality, 2018)
Spiritual care is a greatly misunderstood profession, both conceptually and practically. This misunderstanding was most recently demonstrated in the decision in the Canadian province of Saskatchewan to eliminate all public funds to spiritual care in public healthcare on the grounds of state impartiality with regard to religion. In contrast, this article argues that spiritual care is a secular practice which utilizes religious forms of knowledge to assist the aims of secular state-funded healthcare. Drawing upon such theorists as Jürgen Habermas, Charles Taylor, Paul Ricoeur, and Graham Ward, the article demonstrates that spirituality is the concept employed by secular healthcare to make sense of religious and metaphysical phenomena. As a healthcare profession uniquely suited to address religious and metaphysical concerns using the concept spirituality', spiritual care practitioners are thus shown to be an integral part of the secular healthcare team.